Precarious life : the powers of mourning and violence - Butler, Judith (Verso, 2006)
In her most impassioned and personal book to date, Judith Butler responds in this profound appraisal of post-9/11 America to the current US policies to wage perpetual war, and calls for deeper understanding of how mourning and violence might instead inspire solidarity and a quest for social justice.